(untitled) (REMUNOM, 2025)
ABSTRACT Attention Deficit Hyperactivity Disorder (ADHD) represents one of the main challenges in the contemporary educational context, especially in Mathematics teaching, a discipline that requires a high degree of concentration, working memory, and inhibitory control. This article investigates how gamification, combined with digital resources, can constitute an effective pedagogical strategy to enhance mathematical learning for students with ADHD in middle school. Through a systematic bibliographic review of a qualitative nature, the neuropsychological bases of the disorder are analyzed, with emphasis on executive dysfunctions that impact academic performance, as well as the theoretical foundations of gamification and its application in inclusive educational environments. The results show that gamified strategies, when properly planned and implemented with the support of assistive technologies, promote greater engagement, intrinsic motivation, and self-regulation, favoring the overcoming of cognitive and behavioral barriers. It is concluded that the integration between gamification and digital resources represents a promising path for the inclusion and academic success of students with ADHD, provided it is based on neuroscientific knowledge and aligned with current inclusive education guidelines in Brazil. Keywords: ADHD; Gamification; Mathematics Teaching; Digital Resources; Executive Functions.